2019
DOI: 10.1158/1541-7786.mcr-18-0628
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AXL as a Preclinical Acquired Resistance Mechanism Against Osimertinib Treatment inEGFR-Mutant Non–Small Cell Lung Cancer Cells

Abstract: Osimertinib (AZD9291) has an efficacy superior to that of standard EGFR-tyrosine kinase inhibitors for the first-line treatment of patients with EGFR-mutant advanced non-small cell lung cancer (NSCLC). However, patients treated with osimertinib eventually acquire drug resistance, and novel therapeutic strategies to overcome acquired resistance are needed. In clinical or preclinical models, several mechanisms of acquired resistance to osimertinib have been elucidated. However, the acquired resistance mechanisms… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 47 publications
(46 reference statements)
4
85
0
Order By: Relevance
“…The percentage of AXL‐positive patients was thus 25% (3/12) before EGFR‐TKI treatment and 47% (9/19) after treatment failure, consistent with the previous finding that ~20% of patients showed upregulation of AXL after the development of EGFR‐TKI resistance . Given that AXL has also been shown to confer de novo resistance to EGFR‐TKIs, and a recent preclinical study has shown that AXL expression was increased after resistance to Osimertinib in EGFR mutant cells, the combination of an EGFR‐TKI and an AXL inhibitor may be warranted for EGFR‐TKI–naïve patients and patients with acquired resistance to EGFR‐TKIs.…”
Section: Discussionsupporting
confidence: 86%
“…The percentage of AXL‐positive patients was thus 25% (3/12) before EGFR‐TKI treatment and 47% (9/19) after treatment failure, consistent with the previous finding that ~20% of patients showed upregulation of AXL after the development of EGFR‐TKI resistance . Given that AXL has also been shown to confer de novo resistance to EGFR‐TKIs, and a recent preclinical study has shown that AXL expression was increased after resistance to Osimertinib in EGFR mutant cells, the combination of an EGFR‐TKI and an AXL inhibitor may be warranted for EGFR‐TKI–naïve patients and patients with acquired resistance to EGFR‐TKIs.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, expression of E-cadherin and vimentin was similar in PC9 and PC9-ER cells Figure 2D), with PC9-ER cells having a lower invasion potential than their parental counterparts (0.52 relative invading fraction in PC9-ER compared to PC9 parental cells; Figure 2E). Similar results were previously reported by others: PC9 cells with acquired resistance to osimertinib maintained epithelial phenotype, while H1975 osimertinib-resistant cells developed mesenchymal features [28][29][30]. Overall, two out of three EGFR TKI-resistant models we developed (H1975-OR and SH416-ER) underwent EMT.…”
Section: Egfr Tki Resistance Is Associated With Emtsupporting
confidence: 90%
“…This is an important discovery since it points towards a potential opportunity to utilize vitamin D-based combination therapies in the setting of progressive disease. As a mechanism of resistance to EGFR TKIs, EMT is commonly observed in pre-clinical models [7,[27][28][29][30]44]. In the clinic, EMT is believed to cause EGFR TKI failure in a small proportion (~6%) of EGFR-mutant LUAD patients [4].…”
Section: 25(oh)2d3 Is Known To Induce Transcription Of Multiple Celmentioning
confidence: 99%
“…Osimertinib resistant can occur via oncogenic shift to alternative RTKs including c-MET (11), HER2 and/or HER3 (7-9), IGF1R (12), and AXL (13)(14)(15)(16). The variety of RTK bypass pathways that can lead to osimertinib resistance suggests that broad inhibition of RTK signaling may be a more effective therapeutic strategy than any individual RTK inhibitor to limit Combining osimertinib with a MEK inhibitor can enhance osimertinib efficacy (10,17,20,56,57) and Phase II clinical trials are currently underway to assess combining osimertinib with the MEK inhibitor selumetinib in EGFR-mutated NSCLC (NCT03392246), although resistance to combined osimertinib and MEK inhibition still occurs (17).…”
Section: Discussionmentioning
confidence: 99%
“…The most common EGFR-independent resistance mechanisms involve reactivation of the RTK/RAS/effector pathway (10), often via enhanced signaling through parallel RTKs (7)(8)(9)(11)(12)(13)(14)(15)(16). Here, combining osimertinib with individual RTK inhibitors can both inhibit the development of resistance through the inhibited RTK and kill cancer cells with resistance driven by the specific RTK being inhibited.…”
Section: Introductionmentioning
confidence: 99%